From early conversation to digital performance: Building public speaking confidence among Islamic elementary students in Indonesia - Taufikin, Taufikin (Bulletin of Educational Management and Innovation, 2024)
Background: In an increasingly digitized global educational landscape, public speaking has become an essential competency. However, at the elementary education level—particularly in Islamic education—the development of public speaking confidence is often overlooked and treated as an advanced skill, with limited integration into digital pedagogical practices. Purpose: This study aims to analyze how public speaking confidence can be built from an early age through the integration of daily conversations, video production, and digital distribution, and to formulate a pedagogical model that systematically explains this process. Method: A qualitative case study was conducted at MI Tahfidzul Qur’an Raudlatul Falah, Pati. Data were collected through participant observation, interviews with 5 teachers, 5 parents, 15 students, and 1 religious’ leader (Kiai), as well as the analysis of 20 student videos from July 2023 to January 2024. Analysis was conducted using inductive thematic analysis. Findings: The results of the study indicate that students’ confidence is developed through a recurring pedagogical cycle of “speak–record–publish,” supported by performative transformations (vocal, nonverbal, and structural) and multi-actor social interaction networks. A synthesis of these findings yields a new model, the Digital Performative Habitus Model, which asserts that confidence in speaking is the result of integrating experience, visual reflection, and social validation within a digital learning ecosystem.